The Role of Communication Through Leaflets in Emergency Management and Information Dissemination When a Disaster Occurs in Pasir Lapangan Village - Riko Hengki Nababan; Herlina Tarigan; Tita Aurellia (Institute Of Computer Science (IOCS), 2025)
Indonesia is highly vulnerable to disasters, including the coastal areas of Pasir Lapangan Village, Sibolga City, which are prone to tidal flooding and tsunamis. This study aims to determine the role of communication through leaflets in emergency management and the dissemination of disaster information to the public. The research method used was descriptive quantitative with a sample of 90 respondents (10% of the population of 845 families). The results showed that the use of leaflets has a significant role in three phases of disaster management: mitigation (visual education), preparedness (emergency numbers), and response (quick guides). The use of pictograms proved more effective and easier to understand than long text. The study concluded that optimizing leaflets is crucial in reducing response time and increasing the resilience of coastal communities